Strategi Memperoleh Agent dalam Perdagangan International - Suhendra Suhendra; Adrian Irnanda Pratama (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This research aims to find out how the strategy of business actors in Bengkalis Regency can get agents or buyers in international trade, to find out what are the obstacles for business actors in obtaining agents or buyers in international. This study uses a qualitative descriptive method, which is to explain systematically and describe accurately and clearly. Data collection techniques used in this research are by using interviews, observation, and documentation.The results of research that have been carried out from CV Tuah Bersama and CV Sinar Romindo Indah show that the strategy to get buyers or agents is to survey directly or come to Malaysia. In addition, another method used is by surveying the market there, by providing examples of products that will be sold to agents where the agents obtained are general agents. As for how to maintain agents that need to be done, namely maintaining quality, communicating with each other and giving trust to agents. The main consideration of these two CV Are to take an agent in Malaysia because of the Economic and Market Infrastructure.